Cosmetically Applicable Soluble Agonists for Toll-like Receptor 2 Produced by Fermentation of Asparagus Extract Supplemented with Skimmed Milk Using Lactobacillus delbrueckii subsp. lactis TL24 Consist of Molecules Larger than 100 kDa and Can Be Stabilized by Lyophilization with Dextrin - Yasuhiko Komatsu; Kanako Matsunaga (Molecules)
Cosmetically applicable soluble agonists for Toll-like receptor 2 (TLR2), which can strengthen skin barrier function, were produced by fermentation of asparagus (Asparagus officinalis L.) extract supplemented with skimmed milk using Lactobacillus delbrueckii subsp. lactis TL24. Their molecular size was estimated to be >100 kDa. Their TLR2-stimulating activity was stable over 1 year at 4 °C, but it decreased by more than 95% within 10 and 4 months at 25 °C and 40 °C, respectively. The possibility of stabilization of TLR2-stimulating activity by powdering was tested, and we found that lyophilization with 10% or a higher amount of dextrin could stabilize the activity even at 40 °C. The powdered fermented product dose-dependently stimulated TLR2. It augmented the formation of tight junctions in normal human keratinocytes, as detected by fluorescence staining of occludin and ZO-1, whereas their protein and gene expression levels did not increase, suggesting that a change in subcellular localization of these proteins without significant changes in their amounts might be responsible. The powder nature has some benefits over the aqueous, besides stability, e.g., it can be dissolved just before application, allowing fresh material to be used each time, and it may widen a range of cosmetic applications in non-aqueous types of cosmetics.